Analisis Pemahaman Konsep Mahasiswa pada Topik Vektor - Kurniawan, Bakhrul Rizky; Saputri, Diana Eka; Shoiqin, Muhammad Ibnu (Universitas Nusantara PGRI Kediri, 2019)
This study reveals students' understanding of vectors related to the addition of vectors, vectors and vector units. To achieve these objectives, three formatted question sections are actually packaged in an android application. Each section consists of three questions that discuss different subtopics. Part 1 discusses the subtopic vector addition, part 2 discusses vectors and part 3 unit vectors. This research was conducted at 40 years of undergraduate students of Physics Education, State University of Malang. The results of the analysis show that students have an understanding of good addition vectors in subtopics, but still weak in subtopics storing vectors and arranging large vectors based on unit vectors.